Bringing cultural changes to mental health services through organisational development: an instrumental case study of how a mental healthcare trust in England responds to race-related equality policy in the provision of mental health services - Hussain, Basharat (2015)
This thesis presents an instrumental case study of a National Health Service (NHS) mental healthcare trust in relation to race related equality policy in the delivery of secondary mental healthcare in England. The study takes a constructionist ontological position, and an interpretivist epistemology. Semi-structured interviews were conducted with the 20 participants working at three different levels of the organisation. These include strategic leaders: Chief Executive Officer, Operational Director, Director of Nursing Quality and Patient Experiences, Director of Learning and Development, Head of Human Resources, Equality and Diversity Lead; service level middle managers: General Manager, Modern Matron, Team leader, Manager of the Recovery College; and frontline practitioners: clinical directors, psychiatrist, occupational therapist, staff nurses, community psychiatrist nurse, Recovery College instructor, all working in an adult mental healthcare setting of the organisation. Narrative interviews were also conducted with eight members of the Pakistani community living in the local service area to gain their perspectives on mental illnesses and mental health services.